Photochemical syntheses, transformations, and bioorthogonal chemistry of trans-cycloheptene and sila trans-cycloheptene Ag(i) complexes. Issue 7 (23rd January 2018) - Fang, Yinzhi; Zhang, Han; Huang, Zhen; Scinto, Samuel L.; Yang, Jeffrey C.; am Ende, Christopher W.; Dmitrenko, Olga; Johnson, Douglas S.; Fox, Joseph M.
Abstract : Synthesis and transformations of AgNO3 complexes of trans -cycloheptene (TCH) and trans -1-sila-4-cycloheptene (Si-TCH) derivatives are described. Abstract : A photochemical synthesis of AgNO3 complexes of trans -cycloheptene (TCH) and trans -1-sila-4-cycloheptene (Si-TCH) derivatives is described. A low temperature flow photoreactor was designed to enable the synthesis of carbocyclic TCH derivatives due to their thermal sensitivity in the absence of metal coordination. Unlike the free carbocycles, TCH·AgNO3 complexes can be handled at rt and stored for weeks in the freezer (−18 °C). Si-TCH·AgNO3 complexes are especially robust, and are bench stable for days at rt, and for months in the freezer. X-ray crystallography was used to characterize a Si-TCH·AgNO3 complex for the first time. With decomplexation of AgNO3 in situ, metal-free TCO and Si-TCH derivatives can engage in a range of cycloaddition reactions as well as dihydroxylation reactions. Computation was used to predict that Si-TCH would engage in bioorthogonal reactions that are more rapid than the most reactive trans -cyclooctenes. Metal-free Si-TCH derivatives were shown to display good stability in solution, and to engage in the fastest bioorthogonal reaction reported to date ( k 2 1.14 × 10 7 M −1 s −1 in 9 : 1 H2 O : MeOH). Utility in bioorthogonal protein labeling in live cells is described, including labeling of GFP with an unnatural tetrazine-containing amino acid. The reactivity and specificity of the Si-TCH reagents with tetrazines in live mammalian cells was also evaluated using the HaloTag platform. The cell labeling experiments show that Si-TCH derivatives are best suited as probe molecules in the cellular environment.